LUMBUNG PANGAN MASYARAKAT: KEBERADAAN DAN PERANNYA DALAM PENANGGULANGAN KERAWANAN PANGAN (Forum Penelitian Agro Ekonomi, 2024)
Food barns are the food reserve institution commonly developed in rural areas and play roles in addressing community food insecurity. Food barns exist along with the rice culture and become a part of public food reserve system. The existence of food barns tend to decline due to some, namely: (a) the movement of green revolution which introduces improved rice varieties and agricultural modernization incompatible with the traditional food barn development; (b) the existence of Bulog that plays it role in stabilizing supply of food and rice price which is a disincentive to storing grain; (c) globalization leading to invention of various processed foods distributed to rural areas has changed people’s consumption pattern, and (d) inconsistent and project-oriented technical assistance. Food barns are generally established in the areas accustomed to food insecurity due to lack of access. Food barns may play role to cope with common food insecurity however not capable of dealing with unpredictable food insecurity, e.g. due to disaster. To deal with transient food insecurity it is necessary that the government establishes mobile food reserves such as conducted by Bulog. Food reserves institution is necessary in the autonomy regions along with decreased role of Bulog. Local government’s food reserve institution may be Local Government Enterprises (BUMD), private institution, or collaboration between those of local governments and Bulog. Food insecurity management is also poverty alleviation exertion. Therefore, addressing food security is not only related to food production and provision but it is also infrastructure improvement and human resource development.